The Influence of The Effectiveness of Accounting Information System Utilization, Work Culture, and Incentives on Employee Performance - Anindya Jasmine Kayla (Green Publisher Indonesia, 2024)
Employee performance is one of the criteria for an organization to achieve success. There are several factors that can influence employee performance, including the effectiveness of AIS, work culture, and incentives. This study aims to provide empirical evidence regarding the impact of the effectiveness of AIS, work culture, and incentives on employee performance at PT. Agung Toyota in Bali. The study uses a quantitative approach with a questionnaire to collect data. The population in the study consists of all employees who use the AIS. Sample of 74 successful respondents was drawn using purposive sampling. The analysis technique used was linear regression analysis. Based on the hypothesis test, it was found that the effectiveness of accounting information systems, work culture, and incentives have a positive impact on employee performance.